A comparative analysis of chemical compositions in Camellia sinensis var. puanensis Kurihara, a novel Chinese tea, by HPLC and UFLC-Q-TOF-MS/MS. (1st February 2017) - Li, Yi-Fang; Ouyang, Shu-Hua; Chang, Yi-Qun; Wang, Ting-Mei; Li, Wei-Xi; Tian, Hai-Yan; Cao, Hong; Kurihara, Hiroshi; He, Rong-Rong
Graphical abstract: Highlights: Chemical compositions in Puan tea were analyzed by HPLC and UFLC-Q-TOF-MS/MS. Theacrine was the dominated purine alkaloid detected in Puan tea. Puan tea contained B-type procyanidin dimer, trimer and dimer monogallate. Abstract: Camellia sinensis var. puanensis Kurihara (Puan tea) is a kind of ancient tea plant newly found in Jiangxipo and the surrounding areas of Puan County (Guizhou, China). People there always believe that drinking Puan tea is beneficial to the promotion of health and prevention of diseases. However, detailed information on its compositions has not been reported. Therefore, in this study, the varieties and contents of purine alkaloids and polyphenols in Puan tea were identified and determined by HPLC and UFLC-Q-TOF-MS/MS. Our results showed that theacrine, but not caffeine, was the dominated purine alkaloid detected in Puan tea. Meanwhile, Puan tea contained B-type procyanidin dimer, trimer and dimer monogallate, which were not detected in Camellia sinensis, Camellia ptilophylla and Camellia assamica var. kucha . The obtained results could support the local uses of Puan tea in health and nutrition and contribute to the research of tea variety.